The Potential Use of Cold-Pressed Pumpkin Seed Oil By-Products in a Low-Fat Salad Dressing: The Effect on Rheological, Microstructural, Recoverable Properties, and Emulsion and Oxidative Stability - Tekin-Cakmak, Zeynep Hazal; Atik, Ilker; Karasu, Salih (MDPI, 2021)
The cold-pressed pumpkin seed oil by-product (POB) was evaluated for its application as a natural fat substitute and stabilizer in the reduced-fat salad dressings. For this aim, the samples were prepared by combining the xanthan gum (0.2-0.4 g/100 g), POB (1.0-5.0 g/100 g), egg yolk powder (3 g/100 g), and sunflower oil (10-30 g/100 g) in 17 different formulations. The optimization was carried out using response surface methodology (RSM) and full factorial central composite design (CCD). Results showed that all samples presented the shear-thinning (or pseudoplastic) flow behavior with 3.75-16.11 Pa & BULL;s(n) and 0.18-0.30, K and n values, respectively. The flow behavior rheological data were fitted to a power-law model (R-2 > 0.99). The samples with high POB and low oil content showed similar K and n values compared to high oil content samples. Additionally, the dynamic rheological properties and three interval thixotropic test (3-ITT) were determined. The G & PRIME; value was larger than G & DPRIME; in all frequency ranges, indicating viscoelastic solid characteristics in all samples. The optimum formulation was determined as 0.384% XG, 10% oil, and 3.04% POB. The samples prepared with the optimum formulation (POBLF-SD) were compared to low-fat (LF-SD), and high-fat (HF-SD) control salad dressing samples based on the rheological properties, emulsion stability, oxidative stability, zeta potential, and particle size. The oxidation kinetic parameters namely, IP, E-a, & UDelta;S++, and & UDelta;G(++) showed that the oxidative stability of salad dressing samples could be improved by enriched by POB. The results of the present study demonstrated that POB could be considerably utilized as a natural fat substitute and stabilizer in salad dressing type emulsions.
Keywords: fat substitutes; emulsion stability; optimization; oxidative stability; REDUCED-FAT; PHYSICOCHEMICAL PROPERTIES; ANTIOXIDANT ACTIVITY; KONJAC GEL; MAYONNAISE; EXTRACTION; STARCH; VALUES; ANALOG; Food Science & Technology